What's become of her [large type] : a novel - Caletti, Deb (Wheeler Publishing, a part of Gale, Cengage Learning, 2017)
From National Book Award finalist Deb Caletti comes an emotionally riveting story of a woman falling for a man who may be hiding a dangerous secret--perfect for readers of Jodi Picoult and Kristin Hannah. "Guilty people keep secrets." Isabelle Austen returns to her hometown on a small, isolated Pacific Northwest island to take over the family tourism business after the death of her mother, a disapproving parent and a hard woman to love. Feeling lost, Isabelle is also struggling with a recent divorce and wondering if she'll ever come into her own. Then her life takes a surprising turn: The mysterious Henry North arrives on Parrish Island, steps off a seaplane, and changes Isabelle's world forever. From the beginning, their relationship is heady and intense--then Isabelle learns of Henry's disturbing past, involving the death of a fiancé and the disappearance of a wife. Suddenly Isabelle is caught between love and suspicion, paranoia and passion, as she searches for the truth she may not want to find--and is swept into a dangerous game she may not survive. Praise for What's Become of Her "A darkly enchanting romance sinks into a thrilling cat-and-mouse game." -- Kirkus Reviews "Caletti elevates reader discomfort to the maximum in this nuanced suspense novel. . . . The plot builds to a surprising and well-developed conclusion." -- Publishers Weekly (starred review) "As Caletti combines literary fiction with suspense, she keeps readers guessing until the last page." -- Booklist "This is a lush, suspenseful read set in a sleepy seaside town, with both main characters using the locale (and each other) as a means to escape. Caletti's strengths are all on display: the novel is carefully paced, the prose excellent, and the characters (and their ghosts and demons) are realistic and strikingly drawn. Each person's motivations and reliability as a narrator are weighed and considered over the course of the novel, with expectations upended and reevaluated constantly. The build to the climax is relentless, tense and satisfying." -- RT Book Reviews "This is a fast-paced read, with exceptional moments of suspense." --The Book Review Praise for the novels of Deb Caletti "Striking . . . well-written, strongly characterized and emotionally complex fiction." -- Kirkus Reviews (starred review), on He's Gone "Caletti once again combines interesting characters, pitch-perfect dialogue, and an intriguing plot to tell a deeply memorable story. Her latest is a thoughtful exploration of love and marriage and the power of family and friendship to help along the way." -- Booklist, on The Secrets She Keeps